OPTIMALISASI PENGELOLAAN PERSAMPAHAN MELALUI PENERAPAN TEKNOLOGI DAN INOVASI DI KOTA BANDAR LAMPUNG - Mega Muli Utami; Husna Tiara Putri; Asep Nurul Ajiid Mustofa (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
Bandar Lampung has 1,166,066 people, with waste production reaching 946.35 tons/day. The Ministry of Environment and Forestry has nominated Bandar Lampung as one of Indonesia's dirtiest cities. The waste quantity produced increases, but waste management does not run optimally. In addition, the Bakung TPA still applies the open dumping method so that the waste is immediately disposed of without any processing. The processing carried out is merely limited to composting at several sources of market waste. Technology and innovation in waste management continue to formulate, and it can help improve the quality of waste management. Therefore, this study aims to formulate the best strategy for optimizing the waste management system integrated with technology and innovation. This study used a qualitative deductive approach with descriptive analysis and AWOT analysis (AHP and SWOT). It was concluded that the best strategy to optimize waste management in Bandar Lampung City is the defensive strategy. The strategy consists of fulfilling infrastructure and staff according to standards, increasing efforts and maintenance funds by the government and community retribution, waste socialization movements and simultaneous assistance, optimizing existing technologies and innovations, integrating waste management systems, pursuing a waste monitoring movement, and digitizing the waste management system.